2014
DOI: 10.1002/bab.1219
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐senescence effect of FatI gene in goat somatic cells

Abstract: The fatty acid dehydrogenase I (FatI) is able to express in mammalian cells and convert n-6 polyunsaturated fatty acids (PUFAs) to n-3 PUFAs. n-3 PUFA is an important component of the cell membrane and plays an important role in the prevention and control of a variety of human diseases. However, n-3 PUFAs cannot be endogenously synthesized by mammals because they lack the dehydrogenase that converts n-6 to n-3 PUFA. For the time being, gradually matured transgenic technology makes it possible to produce transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Such balance is also applicable when n-3 PUFA are used to manage antioncogenes. A recent study indicated the anti-aging potential of n-3 PUFA that the overexpression of Fat1 , an endogenously synthesizing n-3 PUFA model, in Boer goat fetal fibroblasts reduced the mRNA expression of p16 and p53 [49]. Nevertheless, fish oil mediates apoptosis of tumor cells by promoting the protein expression of p53 [50].…”
Section: Discussionmentioning
confidence: 99%
“…Such balance is also applicable when n-3 PUFA are used to manage antioncogenes. A recent study indicated the anti-aging potential of n-3 PUFA that the overexpression of Fat1 , an endogenously synthesizing n-3 PUFA model, in Boer goat fetal fibroblasts reduced the mRNA expression of p16 and p53 [49]. Nevertheless, fish oil mediates apoptosis of tumor cells by promoting the protein expression of p53 [50].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a subsequent study by these authors indicated that there is no possibility of integration and insertion of the foreign fat-1 gene in transgenic pigs into the genome of wild nontransgenic pigs by suckling or mating . Recently Sun et al (2014) reported that the proliferation and apoptosis of Boer-goat-cultured foetal fibroblasts were not affected, while the senescence of goat somatic cells was inhibited, by overexpression of the fat-1 transgene.…”
Section: Modifications Of the Composition Of Meat Lipidsmentioning
confidence: 99%